2022
DOI: 10.3389/fonc.2022.918830
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinically significant prostate cancer with a multimodal MRI-based radiomics nomogram

Abstract: ObjectiveTo develop and validate a multimodal MRI-based radiomics nomogram for predicting clinically significant prostate cancer (CS-PCa).MethodsPatients who underwent radical prostatectomy with pre-biopsy prostate MRI in three different centers were assessed retrospectively. Totally 141 and 60 cases were included in the training and test sets in cohort 1, respectively. Then, 66 and 122 cases were enrolled in cohorts 2 and 3, as external validation sets 1 and 2, respectively. Two different manual segmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…( 9 ) compared the combination of lesion segmentation and whole prostate segmentation on T2WI and DWI to establish the optimal radiomic methodology. The results showed that the radiomic model based on whole prostate T2WI and lesion DWI achieved the best performance in predicting clinically significant PCa, which was superior to PI-RADS scores ( 9 ). However, Montoya et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 9 ) compared the combination of lesion segmentation and whole prostate segmentation on T2WI and DWI to establish the optimal radiomic methodology. The results showed that the radiomic model based on whole prostate T2WI and lesion DWI achieved the best performance in predicting clinically significant PCa, which was superior to PI-RADS scores ( 9 ). However, Montoya et al.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics is a novel tool that involves extracting quantitative features from medical images using computational algorithms such as machine learning, which can identify new biomarkers and assess the heterogeneity of the disease (8). Recently, radiomics and its combination with machine learning techniques have shown its promise in MRI-based PCa diagnosis, which was superior to Prostate Imaging-Reporting and Data System (PI-RADS) category (9)(10)(11)(12)(13). mpMRI protocol suggested by PI-RADS v2.0 includes T2weighted imaging (T2WI), diffusion-weighted imaging (DWI) and the corresponding apparent-diffusion coefficient (ADC) maps, and dynamic contrast-enhanced (DCE) imaging (14).…”
Section: Introductionmentioning
confidence: 99%
“…Four recent studies that used MRI/PI‐RAD scores for the creation of prediction models have reached the same conclusion 28–31 . According to ROC analysis in all datasets, where it varied from 0.80 to 0.96, Jing et al 28 integrated radiomics signature and PI‐RADS to construct a radiomics nomogram with superior discriminatory capacity, predicting csPCa, which surpassed the subjective evaluation alone of PSA.…”
Section: Discussionmentioning
confidence: 77%
“…Four recent studies that used MRI/PI-RAD scores for the creation of prediction models have reached the same conclusion. [28][29][30][31] According to ROC analysis in all datasets, where it varied from 0.80 to 0.96, Jing et al 28 integrated radiomics signature and PI-RADS to construct a radiomics nomogram with superior discriminatory capacity, predicting csPCa, which surpassed the subjective evaluation alone of PSA. The use of multiparametric-MRI (mpMRI) based nomograms for predicting csPCa showed a slight but significant net benefit in Castellani's DCA compared to those excluding PI-RADS scores, and the AUC for the full model including PI-RADS scores was 0.77.…”
Section: Nomograms Have Been Developed and Validated In Previousmentioning
confidence: 99%
“…All included papers have been published since 2015, with an increase from 2019. The most studied organs are the prostate [3] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] (S-Table I), female pelvis [4] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] (S-Table II), and rectum [5] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] (S-Table III), while a lower number of publications were related to the liver [6] , [70] , [71] , [72] , [73] , [74] , [75] (S-Table IV), and a miscellaneous group of organs including kidney [76] , [77] , …”
Section: Resultsmentioning
confidence: 99%